Design of Mandala Art Combination with Malay Deli Ornaments - Panjaitan, Nurul Atika Hariani; Tanjung, Mhd. Rusdi (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2023)
Mandala Art literally comes from Sanskrit which means circle. The circle in question is a picture of the cosmos, which describes the whole, unity/oneness, continuity, endlessness, as well as a picture of a sacred space, a transcendent and immanent unity. A circle created to represent wholeness personally and cosmologically. Malay ornament motifs are basically sourced from nature, such as flora, fauna, diamonds and celestial objects. These natural objects are engineered in several specific forms and various types. The design of Mandala Art combined with Malay Deli ornaments is to raise the shape and type of Malay ornaments in making the concept of the Mandala Art pattern. The design of Mandala Art in combination with Malay Deli ornaments is the result of a modern Pattern design based on ideas of motifs or decorative ornaments designed in the form of soft files. The purpose of this design is as a reference for designers, art workers, lovers of Mandala Art, especially traditional Malay Deli applied art.